Toughening Polyamidoamine Hydrogels through Covalent Grafting of Short Silk Fibers - Filippo Maggi; Amedea Manfredi; Federico Carosio; Lorenza Maddalena; Jenny Alongi; Paolo Ferruti; Elisabetta Ranucci (Molecules, 2022)
Linear amphoteric polyamidoamines (PAAs) are usually water-soluble, biodegradable and biocompatible. Crosslinked PAAs form in water hydrogels, retaining most of the favorable properties of their linear counterparts. The hydrogels prepared by the radical post-polymerization of the oligo-α,ω-bisacrylamido-terminated PAA called AGMA1, obtained by the polyaddition of 4-aminobutylguanidine (agmatine) with 2,2-bis(acrylamido)acetic acid, exhibit excellent cell-adhesion properties both in vitro and in vivo. However, due to their low mechanical strength, AGMA1 hydrogels cannot be sewn to biological tissues and need to be reinforced with fibrous materials. In this work, short silk fibers gave excellent results in this sense, proving capable of establishing covalent bonds with the PAA matrix, thanks to their lysine content, which provided amino groups capable of reacting with the terminal acrylamide groups of the AGMA1 precursor in the final crosslinking phase. Morphological analyses demonstrated that the AGMA1 matrix was intimately interconnected and adherent to the silk fibers, with neither visible holes nor empty volumes. The silk/H-AGMA1 composites were still reversibly swellable in water. In the swollen state, they could be sewn and showed no detachment between fibers and matrix and exhibited significantly improved mechanical properties compared with the plain hydrogels, particularly as regards their Young’s modulus and elongation at break.